Total Challenge: A Serious Game for Stimulating Cognitive Abilities - Carvalho, Vítor H.; Martins, Tiago; Soares, Filomena; Araújo, Miguel (International Journal of Advanced Corporate Learning (iJAC), 2016)
If properly used, the high potential of student’s digital literacy may revert to the benefit of Education. Education efficiency may lie in applying the concept of “fun” learning that characterizes the so-called “serious game” that promotes the competitiveness. This type of game can also be used to solve or mitigate problems involving health care, more specifically those relating to intellectual disabilities and autism spectrum disorders, within which there is still much study to be performed. In this sense, we present the Total Challenge, a game oriented to learning which stimulates cognitive abilities of children, but whose potential can be also used to monitor the progress of people with intellectual disabilities or autism spectrum disorders.